The Role of Heuristic Factors in Investment Performance: Exploring the Market Anomalies in a Volatile Environment - Ullah Malik, Kaleem; Shaukat Malik, Muhammad; Irfan, Muhammad; Mehdi, Hussain (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The literature of heuristic factors and investment performance is less confirmatory. That is why it is quite important to explore and quantify the mediation mechanism of stock market anomalies in a volatile environment. For this research, the data were collected through a survey to stock investors who are actively involved in investing. The findings of this study show that heuristic factors, availability, conservatism, and illusion of control have a significant and positive direct relationship to investment performance. For heuristic factors like anchoring and gambler’s fallacy, there has been an insignificant direct relationship to investment performance. While in indirect relationship to the investment performance, illusion of control and conservatism generate both fundamental and technical anomalies in the market, and they affect the investment performance via technical and fundamental anomalies. Anchoring bias, availability bias and gambler fallacy do not generate both technical and fundamental anomalies in market. Our study result indicates that stock market fundamental and technical anomalies have influenced individual investors’ investment performance.The findings show that there is a significant impact of fundamental anomalies on investment performance.